Pengaruh Kepemilikan Manajerial, Corporate Social Responsibility, Capital Intensity, dan Ceo Overconfidence Terhadap Agresivitas Pajak - Efta Widiyah; Dirvi Surya Abbas; Imam Hidayat (Owner : Riset dan Jurnal Akuntansi, 2025)
Tax aggressiveness refers to actions and strategies taken by individuals or companies to reduce or avoid tax obligations that should be paid. The emergence of tax aggressiveness efforts is because companies assume that taxes are a burden that can reduce net profit. This study aims to determine the effect of managerial ownership, corporate social responsibility, capital intensity and ceo overconfidence on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The documentation technique used in this study is a search for financial report data from manufacturing companies listed on the Indonesia Stock Exchange accessed through the idx website. The analysis method used in this study is panel data regression analysis. The sampling technique uses the Purposive Sampling technique. Based on the predetermined criteria, 17 companies were obtained. These findings indicate that only half of the independent variables are proven to statistically influence tax aggressiveness, thus emphasizing the importance of the role of ownership structure and CSR strategy in corporate tax practices, while capital intensity factors and CEO character have not been proven to be the main determinants in this context. The results of the study show that managerial ownership and corporate social responsibility have a significant effect on tax aggressiveness, while capital intensity and CEO overconfidence do not show a significant effect on Tax Aggressiveness.